Long non-coding RNA DDX11-AS1 promotes the proliferation and migration of glioma cells by combining with HNRNPC - Zijin Xiang (Molecular Therapy: Nucleic Acids, 2022)
Glioma is a malignant tumor of the central nervous system with complex pathogenesis, difficult operation, and a high postoperative recurrence rate. At present, there is still a lack of effective treatment. Long non-coding RNA DDX11 antisense RNA 1 (DDX11-AS1) has been shown to promote tumor development, such as hepatocellular carcinoma, esophageal cancer, etc. However, its molecular mechanism in glioma is poorly understood. In this study, we found that the expression of DDX11-AS1 was elevated in glioma tissues, and patients with high expression of DDX11-AS1 had poor prognosis. DDX11-AS1 was a potential prognostic marker. Functionally, DDX11-AS1 promoted glioma cell proliferation and migration. Mechanistically, DDX11-AS1 interacted with RNA-binding protein heterogeneous nuclear ribonucleoprotein C (HNRNPC) to promote Wnt/β-catenin and AKT pathways and the epithelial-mesenchymal transition process. In summary, our study manifests that the DDX11-AS1/HNRNPC axis may play a vital part in the occurrence and development of glioma, which provides new ideas and therapeutic targets for the diagnosis, treatment, and prognosis of glioma.